The Role of Human Resources Development in Legal Aspects and the Optimization of Human Resource Competence at PT. Hana Cakra Indonesia - Muhlis Fahdiar Sembiring; Taoufan Ilhami (SEAN Institute, 2025)
HR plays a strategic role in facilitating corporate change by ensuring that employees are prepared and capable of handling it. This involves effective communication, training to enhance skills, and building trust in the face of uncertainty that often accompanies change. Furthermore, HR also plays a role in driving innovation within the company. By fostering a culture of innovation that celebrates new ideas and encourages cross-departmental collaboration, HR can facilitate the discovery of new solutions, products, or services that can help the company grow and gain a competitive advantage. By managing change and promoting innovation, HR not only strengthens a company's market position but also improves work quality and employee engagement, which ultimately contributes to the company's long-term success. Therefore, managing change and innovation is at the heart of HR strategy, ensuring the company's adaptation to external and internal changes and creating sustainable added value for the organization. In today's dynamic business world, the role of HRD in improving overall company performance cannot be underestimated. Through careful recruitment and selection practices, continuous employee development, proactive performance management, and planned conflict management and well-being, HRD can create a work environment that is not only productive but also harmonious. By implementing effective human resource development strategies, companies can develop employee capacity and motivation, enabling continued growth and competitiveness in an increasingly competitive marketplace. In this research, HRD is not only a human resource administration manager but also a strategic partner in achieving the company's business goals. HRD is expected to be a proactive agent of change in developing employee potential, creating an inclusive and productive work environment, and adapting to technological developments and workplace trends.